THE GREAT PRETENDER: URETHRAL LEIOMYOMA POSING A DIAGNOSTIC CONUNDRUM - A CASE REPORT - Joshi, Divyanshu; Sarpal, Rajeev; Agarwal, Shikhar; Jumed, Suvit; Pankaj, Kumar; Dutta, Rishin (Student’s Journal of Health Research Africa, 2024)
Background Acute urinary retention (AUR) is a common urological emergency, but it is relatively rare in females. The management of female AUR varies due to the diversity of potential underlying causes, often leading to a lack of consensus in treatment protocols. This case highlights a rare cause of AUR in a female patient, presenting a unique diagnostic challenge. Case presentation A 35-year-old female presented to an outside outpatient department (OPD) with complaints of sudden urinary retention, abdominal pain, painful menses, and a mass protruding from the urethra. Examination revealed a tender, non-reducible mass of 5 x 3 cm at the 12-3 o’clock position of the urethra, with a per urethral catheter in place. Pelvic MRI indicated a well-defined, nodular lesion with altered signal intensity along the anterior aspect of the urethra, consistent with a benign mesenchymal lesion. The patient underwent surgical excision of the mass under regional anesthesia. Histopathological examination confirmed the diagnosis of urethral leiomyoma. Conclusion Urethral leiomyomas are rare, benign tumors that can present with symptoms similar to other urethral pathologies, including AUR. Surgical resection is the definitive treatment, with a low risk of malignant transformation but potential for local recurrence. Recommendation This report emphasizes the need for greater awareness and research into female AUR, especially in developing countries, to improve early diagnosis and management.